7. Echoes of Romanticism in Violin and Piano Sonata No. 2, Op. 45 by Marcel Mihalovici - Analytical Landmarks for an Upscale Interpretation - Florea Augustina (Review of Artistic Education, 2020)
The evolution of the genre of violin and piano sonata in the Romanian composition creation in the first half of the 20th century, marked by the tendency towards getting close to the European musical phenomenon by assimilating stylistic influences of Romanticism, especially, of Enescian Romanticism, distinctly manifesting in Violin and Piano Sonata no. 2, op. 45, by Marcel Mihalovici, one of the most renowned Romanian composers settled in Paris, appreciated by the famous contemporaries, such as M.Ravel, V.d’Indy, F. Poulenc etc. Sonata (1941), preceded by a motto in the sonnet of Romantic poet Gérard de Nerval Myrtho: „Je sais pourquoi lá bas lé volcan s’est rouvert…”, impresses through the high emotional tension, metaphorically expressed by the image of the “woken” volcano, figurative suggestiveness of the musical language, architectonic innovativeness, spectacular capitalization of the violin technique in the formula of a violin-piano choir.